Effect of enzyme supplements on macronutrient digestibility by healthy adult dogs. (18th April 2017) - Villaverde, Cecilia; Manzanilla, Edgar G.; Molina, Jenifer; Larsen, Jennifer A.
Abstract: Some enzyme supplement products claim benefits for healthy dogs to compensate for alleged suboptimal production of endogenous enzymes and the loss of enzymes in commercial pet foods secondary to processing. The objective of the current study was to determine macronutrient and energy digestibility by healthy adult dogs fed a commercial maintenance diet with or without supplementation with plant- and animal-origin enzyme products at the dosage recommended by their respective manufacturers. A group of fourteen healthy neutered adult Beagle dogs (average age 8 years) was divided into two equal groups and fed the basal diet alone and then with either the plant- or animal-origin enzyme supplement in three consecutive 10-d periods; the treatment groups received the opposite enzyme supplement in the third period. Digestibility in each period was performed by the total faecal collection method. Serum trypsin-like immunoreactivity (TLI) was measured at the end of each trial. Data were analysed by repeated measures and the α level of significance was set at 0·05. There were no differences in energy and nutrient digestibility between enzyme treatments. When comparing basal with enzyme supplementation, fat digestibility was higher for the basal diet compared with the animal-origin enzyme treatment, which could be a period effect and was not biologically significant (94·7 v . 93·5 %). Serum TLI was not affected by supplementation with either enzyme product. Exogenous enzyme supplementation did not significantly increase digestibility of a typical commercial dry diet in healthy adult dogs and routine use of such products is not recommended.